Personalized medicine in old age psychiatry and Alzheimer’s disease - Siafarikas, Nikias (Frontiers in Psychiatry, 2024)
Elderly patients show us unfolded lives with unique individual characteristics. An increasing life span is associated with increasing physical and mental disease burden [1]. Alzheimer's disease (AD) is an increasing challenge in old age [2]. AD cannot be cured but it can be treated.The complexity of old age and AD offer targets for personalized medicine (PM). Targets for stratification of patients, detection of patients at risk for AD or for future targeted therapy are plentiful and can be found in several omic-levels.